تحسين جودة التدقيق الداخلي وفق مكون المهنية لإطار الكفاءة الصادر عن "IIA" - حمد، محمد علي حسين; الطائي، سلوان حافظ حميد (الجامعة المستنصرية - كلية الإدارة والاقتصاد, 2023)
يهدف البحث إلى التعرف على إطار الكفاءة الصادر عن (IIA) (مكون المهنية)، وعناصره حيث ظهرت الحاجة لمعرفة مدى التزام التدقيق الداخلي في عينة البحث بإطار الكفاءة الصادر عن (IIA) وتتلخص مشكلة البحث من خلال ضعف التزام التدقيق الداخلي لعينة البحث بمكون المهنية وعناصره للإطار لتحسين جودة أدائه. وبيان أهمية هذه العناصر في تحسين جودة التدقيق الداخلي، بهدف تحسين جودة التدقيق الداخلي وتقليل مخاطر الفساد المالي والإداري في الوحدة الاقتصادية، ولغرض تحقيق أهداف البحث تم تصميم استبانة من عدة محاور تضمنت العديد من الأسئلة التي وجهت إلى العاملين في مجتمع وعينة الباحثين وهم من المدققين الداخليين وبعض الاختصاصات الأخرى، بهدف إثبات فرضية الباحثين في التزام التدقيق الداخلي لعينة البحث بمكون المهنية لتحسين جوده أدائه، وتوصل الباحث إلى جملة من الاستنتاجات أهمها إن الالتزام بمكونات إطار الكفاءة بشكل عام ومكون المهنية وعناصره بشكل خاص يحسن من جودة أداء التدقيق الداخلي في الوحدة الاقتصادية عينة البحث، كما قدم الباحث مجموعة من التوصيات أهمها ضرورة مواكبة التطورات التي طرأت على التدقيق الداخلي، والعمل على تفعيل مكونات وعناصر إطار الكفاءة ومنها مكون المهنية لعينة البحث، لغرض تحسين جودة أداء التدقيق الداخلي. The research aims to identify the competency framework issued by the IIA)) (professional component), and its components, where the need arose to know the extent of the internal audit commitment in the research sample to the competency framework issued by the IIA)) and the research problem is summarized by the weak commitment of the internal audit of the research sample to the professional component and its elements of the framework to improve the quality of its performance. And an indication of the importance of these elements in improving the quality of internal auditing, with the aim of improving the quality of internal auditing and reducing the risks of financial and administrative corruption in the economic unit, and for the purpose of achieving the objectives of the research, a questionnaire was designed from several axes that included many questions that were addressed to workers in the community and the research sample who are internal auditors And some other disciplines, with the aim of proving the hypothesis of the research in the commitment of the internal audit of the research sample to the professional component to improve the quality of its performance. The researcher also presented a set of recommendations, the most important of which is the need to keep abreast of developments in internal auditing, and work to activate the components and elements of the competency framework, including the professional component of the research sample, for the purpose of improving the quality of internal audit performance.
Keywords: الوحدات الاقتصادية -- التدقيق الداخلي -- مكون المهنية -- إطار الكفاءة